Cyclopropene fatty acids in some Malaysian edible seeds and nuts: I. Durian (Durio zibethinus, Murr.) - Berry, Shiv K. (Wiley, 1980)
The aril and seeds of the fruit Durian (Durio zibethinus, Murr.) were examined for their protein content and fatty acid composition by gas liquid chromatography (GLC). The values (area percentage) for fatty acids as methyl esters were: aril=14∶0 (0.91%); 16∶0 (34.13%); 16∶1 (7.10%); 18∶0 (1.21%); 18∶1 (42.14%); 18∶2 (7.85%) and 18∶3 plus 20∶0 (5.69%), Seeds=14∶0 (0.12%); 16∶0 (12.20%); 16∶1 (1.15%); 18∶0 (1.42%); 18∶1 (8.42%); 18∶2 (6.50%); dihydrosterculic acid (2.52%); 18∶3 plus 20∶0 (11.30%); malvalic acid (15.72%); sterculic acid (38.53%) and 22∶0 (1.21%). The germ oil contained the highest amount of sterculic acid. The cooking temperatures employed reduced the malvalic and sterculic acid contents in seeds only by ca. 22% and 19%, respectively.